Pengaruh Kompensasi, Motivasi dan Disiplin Kerja Terhadap Kinerja Karyawan Pada PT. BPR LPN Panampung Kota Bukittinggi - Fary Pratama Putra; Vivi Nila Sari; M. Afuan (Trending: Jurnal Manajemen dan Ekonomi, 2024)
This research aims to determine and attempt to analyze the influence of compensation, motivation and work discipline on employee performance at PT. BPR LPN Panampung Bukittinggi City. This research is a Structural Equation Modeling (SEM) model with the SmartPLS 3.0 analysis tool. The population and sample of this research are employees of PT. BPR LPN Panampung Bukittinggi City. The research results found that there is a positive and significant influence between compensation on employee performance. There is a negative and insignificant influence between Motivation on Employee Performance. There is a negative and insignificant influence between Work Discipline on Employee Performance. There is a joint influence of Compensation, Motivation and Work Discipline on Employee Performance.